Improvement proposal to increase performance by applying redesign of stations and work methods together with a preventive maintenance plan in a LPG bottling machine (LACCEI, 2024)
Performance is synonymous with achieving favorable productivity for the organization. In other words, it is to obtain the maximum results with the minimum use of resources. In the case study, the performance in the LPG cylinder packaging process was 75.88%. However, the productive performance of the sector is 83.47%. This generates a technical gap of 7.59% causing the dissatisfaction of the demand for the production of LPG cylinders. Faced with this situation, a model was created that combines the redesign of stations and work methods with the implementation of a preventive maintenance plan. The objective of the model is to reduce the distances traveled by the material, the amount of paint wasted, labor fatigue in the operators, activities that do not generate value, and failures of the packaging scales. The main results were that the number of balloons leaving the system increased by 68 balloons per hour. Also, the average system time to pack a ball is reduced by 1.88 minutes. In addition, the percentages of balls that drop due to excessive weight and failures are reduced by 5 and 6%